NGO and Waste Management: Learning from Bangladesh - Shahen, Md. Abu (Indonesian Journal of Community Services, 2024)
Waste management is very crucial for the protection of the environment and for keeping living places safe and hygienic. However, this paper tried to explore the exemplify roles of non-government organizations in reducing waste and proper waste management in the municipality area of Bangladesh. This paper was prepared based on qualitative in nature while some KIIs and FGDs were conducted to unveil the impactful roles of NGOs in environment protection through waste management. The paper revealed that NGOs are trying to develop good practices regarding waste management in the municipality area was considered the most polluted and contaminated area compared to other parts of the country. They have funded various types of activities like awareness building activities, practice growing activities, equipment installments like bins, IEC distribution, green club formation, treatment plan establishment, vehicle support for carrying, and disposal points were mentionable. Moreover, people who can play a vital role in waste management, particularly local government representatives and women should be aware. Along with, installing permanent disposal facilities, fixation of waste collection date, developing a market of recycled waste, whistling before collection of waste, bin installation, etc., are needed to make strong the waste management activities in municipality areas of Bangladesh.